PULMONARY HYPERTENSION IN PAEDIATRIC PATIENTS: DATA FROM THE COMPERA-KIDS REGISTRY. Issue 1 (14th December 2015) - Gorenflo, Matthias; Pittrow, David; Huscher, Dörte; Ziesenitz, Victoria; Pattathu, Joseph; Praus, Alexander; Ewert, Peter; Kaemmerer, Harald; Group, COMPERA-Kids Steering Committee Study
Abstract : Background: Pulmonary hypertension (PH/PAH) can have many possible causes in childhood. The aim of the COMPERA registry is the characterization of patients of all ages with PH/PAH and their treatment patterns. Methods: Since June 2013, paediatric patients can be included in the COMPERA registry (ClinTrials.gov: NCT01347216 ) which has originally been established for adult patients with pulmonary hypertension in 2007. Results: Until 2015, 78 patients <18 years (47 Pat <6 years) with pulmonary hypertension were enrolled, of whom 65.4% had PAH due to congenital heart disease (PAH-CHD), 25.6% had idiopathic PAH (iPAH), 3 had persistent PH of the newborn, 2 had PH associated with interstitial lung disease, and two had other PH. The patients were 6.1±6.0 years old, 52.6% girls; NYHA functional class I/II in 55.0%, and III in 42.3%. Mean disease duration after diagnosis was 37.7±55.8 months. Right heart catheterization data were available for 82.1% of the patients. Mean pulmonary artery pressure was 42.8±19.4 mmHg, right atrial pressure was 8.0±8.8 mmHg, cardiac index was 3.6±1.2 l/min/m2. Monotherapy was received by 65.4% of the patients whereas 33.4% of the patients had combination therapy. Phosphodiesterase-5 inhibitors (PDE5I) were administered to 76.9% of the patients, 35.9% of the patients received endothelin receptor antagonists and 3.8% received prostacyclins. About 24% of patients received anticoagulation therapy. Conclusion: The most common form of PH in this study cohort is PAH-CHD, followed by iPAH. Treatment options for children primarily comprise PDE5I. Only a small number of paediatric patients receive anticoagulation therapy.